MEMAHAMI PEMIKIRAN ABDURRAHMAN WAHID (Pendidikan Menjadi Sumber Kebebasan Manusia) - Muhammad Husni; Akh Fahrur Rozi (Jurnal Studi Pesantren, 2022)
Human freedom is Gus Dur's fundamental thinking in giving a broad appreciation of all things, both in human life and in paying attention to the well-being of each individual, man is the only being who has the highest perfection of circumstances in every creation of God. To become a full human being, man must provide enough wiggle room for himself outside and within himself According to Gus Dur Human freedom is not unlimited freedom. But the human freedom that Gus Dur refers to is nothing but freedom that is limited by other human freedoms. Freedom can also be defined as self-determination, the ability to choose and the opportunity to fulfill or obtain that choice. In everyone's life, freedom is an essential element. Freedom in Islamic education makes humans learn about events that occur in themselves, Liberation-based Islamic education is a mirror of human independence. Education seeks to provide assistance to free people in objective lives from oppression that strangles them. Therefore Islamic education has an important role to provide relief assistance to students. Islamic education is a process of forming individuals not only in the field of theology, but also in the social, economic and educational fields. Keywords: Education, Human Freedom